The hawk bandits of Tarkoom / 11. - Abbott, Tony, 1952- (Abbott, Tony, 1952- Secrets of Droon, 2001)
An earthquake has brought a piece of the past back to life! It's a wicked city called Tarkoom, full of sneaky bandits with a plan to upset present-day Droon. Eric, Neal, and Julie need to travel back in time to put the city in its place.